MEANING OF IDIOMATIC - Tatema Telaumbanua (Research on English Language Education (Relation Journal), 2022)
This study aims to analyze the types and meanings of idiomatic expressions. This study was designed in a qualitative research with a descriptive approach. The data of this research are short stories. The procedures used in analyzing the data are classifying, selecting. Based on the data analysis, it was found that there are six types of idiomatic expressions, there are similes, binomials, proverbs, euphemisms, cliches and fixed statements, the last is other languages. Also the readers to use this research as a guide in conducting relevant research to sharpen and enlarge their literal development by trying to understand the overall context of the short story.